Probucol alleviates atherosclerosis and improves high density lipoprotein function - Zhong Jian-Kai; Guo Zhi-Gang; Li Chen; Wang Zhen-Kun; Lai Wen-Yan; Tu Yan (Lipids in Health and Disease, 2011)
Abstract Background Probucol is a unique hypolipidemic agent that decreases high density lipoprotein cholesterol (HDL-C). However, it is not definite that whether probucol hinders the progression of atherosclerosis by improving HDL function. Methods Eighteen New Zealand White rabbits were randomly divided into the control, atherosclerosis and probucol groups. Control group were fed a regular diet; the atherosclerosis group received a high fat diet, and the probucol group received the high fat diet plus probucol. Hepatocytes and peritoneal macrophages were isolated for [3H] labeled cholesterol efflux rates and expression of ABCA1 and SR-B1 at gene and protein levels; venous blood was collected for serum paraoxonase 1, myeloperoxidase activity and lipid analysis. Aorta were prepared for morphologic and immunohistochemical analysis after 12 weeks. Results Compared to the atherosclerosis group, the paraoxonase 1 activity, cholesterol efflux rates, expression of ABCA1 and SR-BI in hepatocytes and peritoneal macrophages, and the level of ABCA1 and SR-BI in aortic lesions were remarkably improved in the probucol group, But the serum HDL cholesterol concentration, myeloperoxidase activity, the IMT and the percentage plaque area of aorta were significantly decreased. Conclusion Probucol alleviated atherosclerosis by improving HDL function. The mechanisms include accelerating the process of reverse cholesterol transport, improving the anti-inflammatory and anti-oxidant functions.